2017
DOI: 10.1021/acsami.7b06910
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Alkoxy-Substituted Difluoroboron Dibenzoylmethane Complexes as Environment-Sensitive Materials

Abstract: The optical properties of meta-alkoxy-substituted difluoroboron dibenzoylmethane dyes were investigated in solution and in the solid state. Meta-alkoxy substitution induced strong intramolecular charge transfer (ICT) from the oxygen-donating substituent to the halide and boron acceptors in the excited state, as compared to the π-π* transition that is observed with para-alkoxy substitution. The optical properties of para- and meta-substituted alkoxy boron dyes were evaluated by calculations, in dilute solution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…Moreover, the host materials need a high T 1 energy to hamper the endothermic triplet energy transfer from the guest, which means a small conjugated structure is preferable for hosts . While the polymer matrix, as an alternative host, can effectively restraint the movements of the guest molecules . Because it not only possesses a large T 1 owing to its nonconjugated structure, but also forms the strong intermolecular hydrogen bonding with guests.…”
Section: Viewpoints On Organic Rtp Materialsmentioning
confidence: 99%
“…Moreover, the host materials need a high T 1 energy to hamper the endothermic triplet energy transfer from the guest, which means a small conjugated structure is preferable for hosts . While the polymer matrix, as an alternative host, can effectively restraint the movements of the guest molecules . Because it not only possesses a large T 1 owing to its nonconjugated structure, but also forms the strong intermolecular hydrogen bonding with guests.…”
Section: Viewpoints On Organic Rtp Materialsmentioning
confidence: 99%
“…Organic luminescent materials have gained extensive attention in recent decades for their wide applications in organic light emitting diodes (OLEDs) [1,2], mechano-chromic materials [3][4][5], chemical or biological sensing and imaging [6][7][8][9][10]. Among these, the organoboron luminogens [11][12][13] are particularly promising for their desirable photophysical and electronic properties, such as high carrier mobility, high molar absorption coefficients and high fluorescence quantum yields [14][15][16]. Their diverse reactivity profiles and high tolerance for structure modification create a great potential for applications of these molecules [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Their diverse reactivity profiles and high tolerance for structure modification create a great potential for applications of these molecules [17][18][19]. In particular, difluoroboron β-diketonates (BF 2 bdks), which are a kind of tetra-coordinate organoboron dye easily obtained through Claisen condensation and modified by the different substitutions at the 4, 6-positions [20], have gained considerable attention for their stability and versatile photophysical properties [7,12,21]. Fraser [22] et al reported the recoverable mechano-chromic luminescence (ML) of the cyan polymorph of the difluoroboron avobenzone, which was confirmed to be facilitated by the slip plane [23] in the structure.…”
Section: Introductionmentioning
confidence: 99%
“…It is relatively easy to fabricate an environment-sensitive sensor array because it can be achieved by adjusting polarity, viscosity, pH, etc. (Vazquez et al, 2005 ; Yang Z. et al, 2014 ; Daly et al, 2017 ) Discriminative optical sensor arrays for proteins were also constructed by changing the pH values and ionic strengths because different proteins usually have different net surface charges, such as negative, positive, or neutral at various pH. Xu et al ( 2010 ) created an array of water-soluble conjugated polymer solutions with six different ionic strengths for protein identification and denaturation detection.…”
Section: Environment-sensitive Sensor Arrays For Protein Recognitionmentioning
confidence: 99%